La construction des appellations viticoles et la géographie juridique - Éric Rouvellac (Développement Durable et Territoires)
Sometimes underestimated alliance, the geography and the law possess an intersection easy to conceive. Territories managed by societies call to the law and define limits asserting the passage of a mode of management in an other one. Guaranteed vintage constitute an example of choice by the implications socioeconomic, which the law can have by structuring a guaranteed vintage and a winemaking territory. We were interested in the case of the area guaranteed vintage of Cahors to show in a very large-scale approach, which is necessary to base the law on the least questionable possible criteria.